Organic Semiconductor Lasers and Tailored Nanostructures for Raman Spectroscopy - Liu, Xin (KIT Scientific Publishing, 2015)
This work presents the application of organic semiconductor distributed feedback laser as free-space excitation source in Raman spectroscopy. Surface-enhanced Raman scattering effect is exploited to improve the detection sensitivity. The SERS conditionis achiedved by using substrates consisting of gold-coated polymeric nanopillar arrays. The organic-laser-excited SERS measurements are applied to verify the concentration variation of biomolecule adenosine in aqueous solutions.